Fotografie e istituzioni museali: il sistema della doppia copia e l’accumulo dei fondi. Le Regie Gallerie di Firenze, 1860-1906 - Binazzi, Marta (Rivista di studi di fotografia. Journal of Studies in Photography, 2020)
Beginning in the late 1850s, photographic companies reproducing artworks kept in the Royal Galleries of Florence were required to submit copies of their work to the Ministry of Public Education and the museum’s director. This paper shows that while photographers obeyed the rule, their photographs were stored away and left mostly unused for over two decades before the process of creating a proper collection began in the 1880s. Countering traditional histories of how photographic collections were constituted, this paper analyzes bureaucratic practices of documentation and questions the status of photographs in 19th century museums.